Rendering Optical and Structural Properties of Semiconductor Nanocrystals by Chemical Doping - Sevim, Seçil; Özçelik, Serdar; Özçelik, Serdar (Izmir Institute of Technology, 2012)
Semiconductor nanocrystals are widely used in technologic applications because of their unusual and tunable optical properties. In this study we synthesized two type of semiconductor nanocrystals by the aqueous synthesis method. Colloidal HgCdTe semiconductor nanocrystals were synthesized by cation exchange reaction at room temperature. The absorption and photoluminescence spectra of water dispersible semiconductor nanocrystals appeared in NIR range of the electromagnetic spectrum. Aging process showed higher shift to red region in absorption and fluorescence spectra for HgCdTe nanocrystals. Increasing the initial Hg:Cd mole ratio spectral tuning was achieved. The size of the semiconductor nanocrystals was controlled between 8 nm to 44 nm by selecting the size of initial CdTe nanocrystals. Water dispersible Gd doped CdTe nanocrystals were also studied by changing initial Cd:Gd mole ratio. CdS shell was formed in order to make more compact and stable Gd doped CdTe nanocrystals. Size of Gd doped CdTe/CdS nanocrystals was tuned up to 38 nm by increasing initial Gd content. The optical spectra of Gd doped CdTe nanocrystals were in the range from 535 nm to 555 nm after 4 hours reaction time. Photoluminescence quantum efficiencies of Gd doped CdTe nanocrystals were measured and found out that doping Gd, decrease the quantum yield of nanocrystals. We concluded that CdTe nanocrystals can be used to synthesize doped nanocrystals by chemical doping. We demonstrated that optical and structural properties of Hg and Gd doped CdTe can be rendered by chemical doping.
Thesis (Master)--İzmir Institute of Technology, Chemistry, İzmir, 2012
Includes bibliographical references (leaves: 46-48)
Text in English; Abstract: Turkish and English
xi, 48 leaves
Keywords: Semiconductor nanocrystals; Nanotechnology